Dampak Servant Leadership Terhadap Pembelajaran Organisasi dan Kinerja Guru: Studi Pada Guru-Guru SMA dan SMK Se-Kota Madiun - Veronika Agustini Srimulyani; Kesia Tripena Hutajulu (Jurnal Manajemen dan Bisnis Indonesia, 2013)
This study aims to examine and analyze the influence of servant leadership to organizational learning and teacher performance, and analyze whether the effect of organizational learning mediate the relationship of servant leadership to teacher performance. The respondent in this study were high school teachers in Madiun, which amounts to 281 people. Research instrument used in testing the validity and reliability. The analysis tool used is simple regression, multiple regression, hypothesis testing device using t test and mediation. Questionnaire as a means of collecting primary data, Likert scale of measurement used by five (5) of alternative answers. Secondary data obtained from institutional documentation. Test results showed that the instrument is valid and reliable research, simple regression produced a positive un-standardized beta for all variables. Hypothesis states that the hypothesis was accepted. The results showed that: (1) servant leadership have positive and significant effect on organizational learning (2) servant leadership have positive and significant effect on teacher performance (3) organizational learning has positive and significant effect on teacher performance (4) Servant leadership had indirect impact on teacher performance with organizational learning as mediating variable. Key Word: Servant Leadership, Organizational Learning, Teacher Performance